CHARACTERIZATION OF ARSENIC TOLERANT RHIZOBIUM Sp. ISOLATED FROM ROOT NODULES OF VIGNA RADIATA - P. VEERABRAMHACHARI; E. KARIALI (The Journal of Research ANGRAU, 2024)
The rationale of the study was to characterize arsenic tolerant Rhizobiumsp. from root nodules of Vigna radiate in the vicinity of the fertilizer production plant contaminated with arsenic. The current investigation involved the interactions of Rhizobium sp. in remediating arsenic has been studied by isolating root nodules of Mung Bean (Vigna radiata) and analyzed for strain characterization, CFU/mL counts, biomass yield, enzymes (cellulase and amylase), and proteins. The screened bacteria were shown to be both arsenic tolerant and sensitive. All isolates were determined to be Rhizobium sp. based on colony, morphology, biochemistry, and nodulation ability analysis. The arsenic sensitivity of the chosen isolates was confirmed by low CFU/mL counts and low biomass output in the medium. The results showed that strain MRR121 is sensitive to arsenic, while strain VBCK1062 showed significant tolerance levels based on the arsenic sensitivity tests. The results emphasized that the sensitivity and tolerance of Rhizobium sp. isolates to arsenate was determined, with reference to their growth and biomass yields, enzyme assays, and protein profiles. The isolated Rhizobium strains exhibited growth retardation when the As concentration was raised beyond 25 mg/mL, as confirmed by the CFU and biomass. The study has clearly evidenced that while increased amounts of arsenic are extremely harmful to the Rhizobium strain The As tolerant strain VBCK1062, outproduced the sensitive strain in terms of proteins and enzymes (cellulase and amylase). Based on the computed similarity coefficient, there is a 76% similarity between the tolerant strain and the commercial (MTCC 616) strains. This study gives better understanding of plant-metal-microbe interactions and hence can be used as a criterion for isolation of As (V) tolerant Rhizobium sp. from metal contaminated agro-geo-ecosystems.